Influence of music on steroid hormones and the relationship between receptor polymorphisms and musical ability: a pilot study - Fukui, Hajime; Toyoshima, Kumiko (Frontiers in Psychology, 2013)
Studies have shown that music confers plasticity to the brain. In a preliminary pilot study, we examined the effect of music listening on steroid hormones and the relationship between steroid hormone receptor polymorphisms and musical ability. Twenty-one subjects (10 males and 11 females) were recruited and divided into musically talented and control groups. The subjects selected (1) music they preferred (chill-inducing music) and (2) music they did not like. Before and after the experiments, saliva was collected to measure the levels of steroid hormones such as testosterone, estradiol, and cortisol. DNA was also isolated from the saliva samples to determine the androgen receptor and arginine vasopressin receptor 1A genotypes. Advanced Measures of Music Audiation (AMMA) was used to determine the musical ability of the subjects. With both types of music, the cortisol levels decreased significantly in both sexes. The testosterone (T) levels declined in males when they listened to both types of music. In females, the T levels increased in those listening to chill-inducing music but declined when they listened to music they disliked. However, these differences were not significant. The 17-beta estradiol levels increased in males with both types of music, whereas the levels increased with chill-inducing music but declined with disliked music in females. The AMMA scores were higher for the short repeat length-type AR than for the long repeat length-type. Comparisons of AR polymorphisms and T levels before the experiments showed that the T levels were within the low range in the short repeat length-type group and there was a positive relationship with the repeat length, although it was not significant. This is the first study conducted in humans to analyze the relationships between the AR gene, T levels, and musical ability.